Identification of deletions in children with congenital hypothyroidism and thyroid dysgenesis with the use of multiplex ligation-dependent probe amplification - Kumorowicz-Czoch, Malgorzata; Madetko-Talowska, Anna; Tylek-Lemanska, Dorota; Pietrzyk, Jacek J.; Starzyk, Jerzy (Journal of Pediatric Endocrinology & Metabolism, 2015)
Thyroid dysgenesis (TD) is the most common cause of congenital hypothyroidism (CH). Important genetic factors possibly contributing to TD etiologies include mutations of thyroid transcription factors and TSHR-encoding genes. Our objective was to determine multiplex ligation-dependent probe amplification (MLPA) utility in detecting the copy number changes in patients with CH and TD. : The study included 45 children from southeastern Poland selected via already established neonatal screening for CH. Genomic DNA was extracted from peripheral blood samples and used in MLPA analysis. Genetic variations were analyzed within selected fragments of the thyroid stimulating hormone receptor and genes. Three heterozygous deletion types in probe hybridization regions were identified for the following genes: (exon 7), (exon 2), and (exon 1). Monoallelic deletions were identified in 5/45 TD subjects. MLPA is a useful tool for copy number changes detection and might both improve and expand genetic analysis for CH and TD.